2014
DOI: 10.4209/aaqr.2013.06.0191
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Approach for the Prediction of Ground-Level Air Pollution (around an Industrial Port) Using an Artificial Neural Network

Abstract: The prediction of air pollution levels is critical to enable proper precautions to be taken before and during certain events. In this paper a rigorous method of preparing air quality data is proposed to achieve more accurate air pollution prediction models based on an artificial neural network (ANN). The models consider the prediction of daily concentrations of various ground-level air pollutants, namely CO, PM 10 , NO, NO 2 , NO x , SO 2 , H 2 S, and O 3 , which were measured by an ambient air quality monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Oman has similar weather conditions as other GCC countries (Table 5). Therefore, infiltrations of outdoor air pollutants from both natural and anthropogenic sources are important factors in determining the IAQ (Baawain and Al-Serihi, 2014). Abdul-Wahab et al (2005) reported the presence of high-level earth metals (Zn, Mg, Fe, and Cu) in homes due to natural dust storms, while limestone borne-aerosols were attributed to nearby cement industries.…”
Section: Ventilations and Building Designsmentioning
confidence: 99%
“…Oman has similar weather conditions as other GCC countries (Table 5). Therefore, infiltrations of outdoor air pollutants from both natural and anthropogenic sources are important factors in determining the IAQ (Baawain and Al-Serihi, 2014). Abdul-Wahab et al (2005) reported the presence of high-level earth metals (Zn, Mg, Fe, and Cu) in homes due to natural dust storms, while limestone borne-aerosols were attributed to nearby cement industries.…”
Section: Ventilations and Building Designsmentioning
confidence: 99%
“…Several studies have been conducted around the world that investigate the air quality in industrial areas in terms of various pollutants such as volatile organic compounds [2] , trace elements [3] , air pollution indices (including SO 2 , NO 2 , PM 10 ) [4] and others. Some of these studies have attempted to predict future air pollution levels through detailed monitoring [5] .…”
Section: Introductionmentioning
confidence: 99%
“…One solution is to apply Fuzzy Logic techniques [24], [25]. Another is to apply a variety of neural network procedures [11], [12]; among the most useful being Radial Basis Function and Elman Networks [13], as well as the latest recurrent types [14]- [16]. In article [17], the accuracy of prediction of PM10 pollution by wavelet transformation and an ensemble of neural predictors is considered.…”
Section: Introductionmentioning
confidence: 99%